Your emotions, yourself a guide to your changing emotions - Virtue, Doreen 1958-; Brokaw, Tanya (Los Angeles Lowell House Juvenile Chicago Contemporary Books, 1996)
Examines some of the feelings experienced by young people and discusses how to deal with painful emotions and get help when needed.
Includes index.
Keywords: Emotions in children -- Juvenile literature; Emotions in adolescence -- Juvenile literature; Emotions